(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
The religious dimension in fighting terrorism: the Austrian case ABSTRACT: Following the terrorist attack that occurred in Vienna on the night of the 2nd of November 2020, the Austrian government has approved an innovative package of measures with the intent of countering radicalization and terrorism. After introducing the context that led to the approval of the abovementioned legal tool, the paper aims to explore the content of some specific laws introduced with it. Focusing on two of the most relevant innovations, the new crime of religiously motivated extremist association and the amendment to the Islam Act 2015, an emphasis is put on the relationship between the new package and the freedom of religion. SOMMARIO: 1. Introduzione: la libertà di religione austriaca - 2. Le premesse al pacchetto antiterrorismo - 3. Le innovazioni in ambito penalistico - 4. In particolare, il paragrafo 247b: il reato di Islam politico - 5. Il reato di associazione estremista a motivazione religiosa. Un’analisi critica - 6. Il pacchetto antiterrorismo e la legge sui rapporti con la comunità religiosa islamica - 7. Conclusioni: l’impatto del pacchetto antiterrorismo sull’esercizio della libertà di religione.